Effects of the COVID-19 Pandemic on the Perception of Inclusion in School Education and Physical Activity Among Polish Students - Kostorz, Karolina; Zwierzchowska, Anna; Ziemba, Mateusz (Frontiers in Psychology, 2022)
The COVID-19 pandemic impacted children and adolescents’ lives, leading to many changes in their routines, especially in education. Face-to-face physical education (PE) classes during COVID-19 were affected in organization, possibly conditioning students’ participation, motivation and learning. In the extreme conditions of the coronavirus, it may be assumed that a daily physical activity is much less than before, partly because pupils are learning outside the school environment and a PE lessons taught using remote forms does not fulfil its activation. The aim of the study was to assess the pupil’s perception of inclusion in school education during the remote learning caused by COVID-19 pandemic and to compare results with the control group. Moreover, the physical activity of respondents during social isolation due to the coronavirus was examined. The sample consisted of 111 pupils both genders, aged 14-21. The Perceptions of Inclusion Questionnaire (PIQ) was used to measure perception of inclusion in school education. The structure of the participants’ physical activity was examined using the International Physical Activity Questionnaire-Long Form (IPAQ-LF) for adolescents. It was observed that the pupils’ gender did not differentiate their perception of inclusion in school education. It was proved that respondents participating in research during the COVID-19 pandemic obtained a statistically significantly lower results in the case of ‘emotional well-being in school’ (p < 0.001; η2 = 0.07), but higher mean in relation to ‘social relationships with other pupils (p = 0.04; η2 = 0.02) than the control group. Girls achieved a higher mean in the case of walk MET (p = 0.02; η2 = 0.06) than boys. Additionally, it was observed that the recommendation of vigorous physical activities was achieved by 37.78% boys and 34.85% girls. In turn 69.70% female pupils and 77.78% male respondents met the recommendations for medium physical activities. It was also noted that 87.88% girls and 86.67% boys participating in the research was achieved recommendation for total physical activities. The analysis showed negligible and low positive correlations between examined variables.